BOOSTING SPEAKING SKILL THROUGH GAME ONLINE IN STUDENTS’ MADURA UNIVERSITY - Rikzen Alfarosi (Universitas Madura, 2023)
Speaking is complex skilll that express the ideas,opinions,desires,our fellings freely,structured and spontaneously that aim give or get information and knowledge from other people.The speaking process base on experiences that can be obtained through discusiion,reading,obsrvation, and listening.All the students want to speak English fluently, therefore students must learn to boosting their speaking skills. Talking about Speaking boosting, the boosting is divided into several aspects ranging from boosting pronounciation,comprehension, grammar, and vocabbulary. It can be used as a measurement our speaking is good or not..almost all students have method to boosting English speaking skill namely Online game. The studennts was familiar with gadgets rarely have online games, not only one but more online games on one gadget.This researcher have research the student of english department in academic year 2017-2020 with using interview method. The result of the study is can boosting speaking skill but not efeective to be Media learning in English program students Madura University.